(untitled) (Nigerian Journal of Technology, 2013)
A pioneer palm oil boiler unit, in an immense power self-contained oil mill, impaired by many years of accumulated depreciation, was rebuilt in the pattern of a design-out scheme aimed primarily at rehabilitating the entire boiler system to a state of functionality. The research work studied the pre-maintenance and post maintenance performance relativities through statistical analysis of data collected and also developed Failure Mode and Effect Analysis (FMEA), and Fault Tree Analysis (FTA) worksheets for the boiler unit. It is hypothesized that the pressure build up and discharge rates in a boiler system is normally distributed under normal operational mode. The effectiveness of the maintenance work carried out on the boiler enhanced the processing capability of the entire plant. The study revealed that under a single shift operating mode (8 hours), a time saving of 72 minutes arising from the effectiveness of the plant overhaul carried out is achieved.